2016
DOI: 10.4103/0972-5229.180042
|View full text |Cite
|
Sign up to set email alerts
|

Intensive Care in India: The Indian Intensive Care Case Mix and Practice Patterns Study

Abstract: Aims:To obtain information on organizational aspects, case mix and practices in Indian Intensive Care Units (ICUs).Patients and Methods:An observational, 4-day point prevalence study was performed between 2010 and 2011 in 4209 patients from 124 ICUs. ICU and patient characteristics, and interventions were recorded for 24 h of the study day, and outcomes till 30 days after the study day. Data were analyzed for 4038 adult patients from 120 ICUs.Results:On the study day, mean age, Acute Physiology and Chronic Hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
63
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(72 citation statements)
references
References 35 publications
(38 reference statements)
6
63
3
Order By: Relevance
“…[28] Also spending power is more in higher socioeconomic class, therefore bearing the expense of costly treatments of critical care is also more in this group and least in low socioeconomic group. [25] Similar finding was encountered in our present study when we found that majority of this class gave a positive history of alcoholism or smoking or both, in some cases. Maximum deaths occurred in age group 31-50 which differs from finding of other such studies.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…[28] Also spending power is more in higher socioeconomic class, therefore bearing the expense of costly treatments of critical care is also more in this group and least in low socioeconomic group. [25] Similar finding was encountered in our present study when we found that majority of this class gave a positive history of alcoholism or smoking or both, in some cases. Maximum deaths occurred in age group 31-50 which differs from finding of other such studies.…”
Section: Discussionsupporting
confidence: 92%
“…This finding is in corroboration with findings of other studies conducted in other parts of globe. [24,25] One of the reason in of this high ratio in our hospital might be attributed to rural population in our area. Being a rural healthcare setup major chunk of deceased patients belonged to low socioeconomic class.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…A multi center observational point prevalence study (INDICAPS) conducted in India had patients with moderate severity of illness as evidenced by APACHE II of 17.4(SD±9.2). 20 This signifies that there is a need for improvements in the organization and delivery of critical care in Indian ICUs. APACHE score is declared the "gold standard" for the evaluation of intensive care and is one of the most commonly used scoring system in intensive care unit around the world.…”
mentioning
confidence: 99%
“…Overall studies from abroad and India reported to have ICU length of stay between 3-11 days. [20][21][22] Therefore the main goal of the health system should focus on cost reduction by decreasing the length of stay both in ICU and hospital by providing a system of patient centered quality care.…”
mentioning
confidence: 99%